From Listening to Hearing the Message - Janez Vodičar (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Evangelizing is searching for an appropriate language to hand on Revelation. Demonstrated is a possible use of linguistic theories and educationally-developmental understandings of Vigotsky, to reach an increasingly isolated human. A self- centered human being (autologous) has a difficult time understanding others and is thus becoming more empty-like he has no purpose. Evangelizing, which brings Revelation, a language of Another, becomes necessary to free the modern human for dectological sphere. Even though authology has become a part of approaches of evangelization, pastoral care has to become more dectological. The possibility of becoming open to transcendental in immanence of a subject is shown through three types of passivity in the philosophy of P. Ricoeur. Thus we see compatibility of new methods of evangelizing with the old ones. The best solution for modern evangelizing is shown in the community of the Church, which contains all of the necessary language for accepting the revelation of God as well as our neighbor. This way our God and our neighbor will be heard in the world, which firmly stands by freedom and autonomy.